2019
DOI: 10.34172/ijbsm.2019.05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Global Postural Reeducation Exercise on Pain and Hip Muscle Flexibility in Patients with Chronic Low Back Pain and Movement Control Dysfunction

Abstract: Introduction: Patients with non-specific low back pain (NSLBP) and movement control dysfunction demonstrate alternation in hip muscles flexibility and spinal movement patterns. Therapeutic modalities that augment hip muscles flexibility could help these patients. The aim of this study was to investigate the effect of global postural reeducation (GPR) on pain and hip muscle flexibility in patients with NSLBP and movement control dysfunction. Materials and Methods: A total of 27 men with a mean age of 31.21±2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…In the GPR method, stretch is done in the opposite direction and there are no possible compensations while performing a decompression action (16,25). Our study findings about the improvement of hip muscle flexibility were consistent with the results reported by Sheikhi, who indicated that GPR exercises significantly increased hamstring muscle flexibility in patients with chronic NSLBP and MCI (29). The insignificant effects of both training protocols on the improvement of other hip muscles flexibility observed in this study may have been attributed to the short duration of the exercise program.…”
Section: Discussionsupporting
confidence: 88%
“…In the GPR method, stretch is done in the opposite direction and there are no possible compensations while performing a decompression action (16,25). Our study findings about the improvement of hip muscle flexibility were consistent with the results reported by Sheikhi, who indicated that GPR exercises significantly increased hamstring muscle flexibility in patients with chronic NSLBP and MCI (29). The insignificant effects of both training protocols on the improvement of other hip muscles flexibility observed in this study may have been attributed to the short duration of the exercise program.…”
Section: Discussionsupporting
confidence: 88%
“…34 The results of a study by Sheikhi indicated that GPR exercises significantly reduced pain in patients with chronic NSLBP with movement control dysfunction. 35 In line with the results of other studies, the present study has shown that performing stability exercises leads to a reduction in pain and disability in people with chronic LBP 36 and reduces the recurrence of LBP. 37 It seems that the basis of LSE is to adapt to the proprioception sense that receives stimuli in high-risk situations.…”
Section: The Standing Posturesupporting
confidence: 91%
“…In this sense, from a methodological point of view, this study is aligned with the recommendations of intervention with GPR used in different studies such as Amorim et al ( 50 ), Brooks et al ( 51 ), and Kloek et al ( 52 ). However, we can contrast the results with other studies focused on older people, children, or special populations and using interventions of different durations ranging from 6 weeks ( 53 ) to 12 weeks ( 54 ). Therefore, it would be interesting to expand GPR studies focusing on physiological and cognitive variables such as sleep quality and stress to determine the best protocols.…”
Section: Discussionmentioning
confidence: 98%